Associations of Current, Childhood, and Adolescent Milk Intake with Serum Insulin-like Growth Factor (IGF)-1 and IGF Binding Protein 3 Concentrations in Adulthood. (18th August 2019) - Srinivasan, Vishnu; Nimptsch, Katharina; Rohrmann, Sabine
Abstract: Previous studies have shown that insulin-like growth factor (IGF)-1 levels are positively and IGF binding protein (IGFBP)-3 levels negatively associated with risk of certain cancers. Also, dietary factors may influence the IGF system. We aimed to analyze the associations of current, childhood and adolescent milk intake with IGF-1 levels, IGFBP-3 levels and IGF-1:IGFBP-3 molar ratio in adulthood. Multivariable linear regression analyses by sex and race/ethnicity were performed using cross-sectional data from the Third National Health and Nutrition Examination Survey. A total of 5, 805 participants were included in the analyses. Adult IGF-1 levels and IGF-1:IGFBP-3 molar ratio had significant inverse associations ( P -trend = 0.02) with adolescent milk intake in non-Hispanic white men, but not in men of other race/ethnicities or in women. There were no associations between current or childhood milk intake and IGF-1 levels or IGF-1:IGFBP-3 molar ratio in adulthood. Current milk intake and childhood milk intake had significant positive associations ( P -trend = 0.02) with adult IGFBP-3 levels in non-Hispanic white and non-Hispanic black women, respectively, but no associations were observed in Mexican American women or in men. Overall, there were long-term and short-term associations between milk intake and IGF-1 and IGFBP-3 levels, but the associations varied by race/ethnicity and sex.